Upfront & Personal - Nolan, Coleen (London Sidgwick & Jackson, 2009)
An autobiography of Coleen Nolan. It describes her eventful life, from joining her sisters' band The Nolans when she was only nine to growing up in the spotlight. It shows how she coped with her tumultuous marriage to television star Shane Richie and how, after they split she was left a single parent struggling to get through each day.
Include Color Illustration
Keywords: Singers -- Television personalities -- Women singers